If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 35 = 9y + -7 Reorder the terms: 35 + 2y = 9y + -7 Reorder the terms: 35 + 2y = -7 + 9y Solving 35 + 2y = -7 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 35 + 2y + -9y = -7 + 9y + -9y Combine like terms: 2y + -9y = -7y 35 + -7y = -7 + 9y + -9y Combine like terms: 9y + -9y = 0 35 + -7y = -7 + 0 35 + -7y = -7 Add '-35' to each side of the equation. 35 + -35 + -7y = -7 + -35 Combine like terms: 35 + -35 = 0 0 + -7y = -7 + -35 -7y = -7 + -35 Combine like terms: -7 + -35 = -42 -7y = -42 Divide each side by '-7'. y = 6 Simplifying y = 6
| n=3+3 | | 2x+42=x+42 | | 2(v-6)-(-3+6)=1-2v-2v | | 2s-10=s-2 | | 4(x^2-5x+7)-8(x^2+3x-2)= | | s-1.59=10.31 | | 2x+22=x+22 | | 800=10(15)+20y | | 1/10(x+1)= | | 3y=91+2x | | 2*3-2*x=2(3-11) | | P-18=45 | | h+1.6=5.09 | | 3(sin(X))=cos(X) | | 4-4tan^2x=0 | | 2x-3-5=8 | | D+20=2.5 | | 8lnx=7 | | 8x^2-34x-9=0 | | 3.5=z/3 | | 5m-3(-7m+4)= | | 7x+10=100 | | k+13.63=15.63 | | 3x+4=2x+18 | | x-(0.2*x)=10000 | | f+1=3 | | K-14=12 | | (5x-26)x=63 | | 3(r-5)=13 | | c+20=35 | | 5m-16-8m=23 | | -6u^2-11u-4=0 |